Where Do We Stand in the Domestic Dog (Canis familiaris) Positive-Emotion Assessment: A State-of-the-Art Review and Future Directions - Csoltova, Erika; Mehinagic, Emira (Frontiers in Psychology, 2020)
Although there have been a growing number of studies focusing on dog welfare, the research field concerning dog positive emotion assessment remains mostly unexplored. This paper aims to provide a state-of-the-art review and summary of the scattered and disperse research on dog positive emotion assessment. The review notably details the current advancement in the dog positive emotion research, what approaches, measures, methods, and techniques have been implemented so far in emotion perception, processing, and response assessment. Moreover, we propose possible future research directions for short-term emotion as well as longer-term emotional states assessment in dogs. The review ends by identifying and addressing some methodological limitations and by pointing out further methodological research needs.